GRAZING HABITS OF ONE HORNED RHINOCEROS (RHINOCEROS UNICORNIS) IN POBITORA WILDLIFE SANCTUARY OF ASSAM (Indian Journal of Animal Production and Management, 2013)
In order to successful translocation and in-situ conservation of one horned rhinoceros (Rhinoceros unicornis), some baseline studies in natural condition are highly essential. The objective of this study was to understand the grazing habits and the preference of fodder of rhinos in natural condition. The data were collected from Pobitora Wildlife Sanctuary of Assam by scan sampling methods with the help of an ethogram. The results showed that grazing both in grassland and wetland (30% and 22% of total observations) were the primary activities of rhinos during 24 hours. There was seasonal variation in grazing habit. Animals spent maximum time in grazing both in grass (45.68%) and wet land (40.74%) during post monsoon season in comparison to the other seasons. About 11 species of grasses were identified as preferred fodder of rhinos of Pobitora Wildlife Sanctuary. The proximate composition of these grasses revealed that they contain 80-85% moisture, 6-15% crude protein and 10-15% ash.
Keywords: Rhinoceros unicornis; Sanctuary; Grazing; Ethogram